2004
DOI: 10.5558/tfc80718-6
|View full text |Cite
|
Sign up to set email alerts
|

An examination of value-added and variable cost trends across Canadian forest regions and sectors

Abstract: Value-added forestry has received much attention in the past few decades as a means of generating more output value for a given timber input. The growth in value-added production in the forest industry is directly affected by changing forest output/input prices, technology, investment strategies, government policies, and a host of other factors. Since many of these factors are unique to each forest region and sector in Canada, it is expected that one would observe a number of different value-added and variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…A final area of market price analysis in which I have been involved concerns value-added production in the forest industry. In 2004, I conducted a study examining value-added and variable cost trends in five regions and three sectors of the Canadian forest industry over the 1970 to 1995 period (Lantz 2004). Using regression analysis, I found that a number of sectors and regions exhibited favourable value-added and variable cost trends over time.…”
Section: Research Contributions To Valuing Multiple Forest Outputs Mamentioning
confidence: 99%
“…A final area of market price analysis in which I have been involved concerns value-added production in the forest industry. In 2004, I conducted a study examining value-added and variable cost trends in five regions and three sectors of the Canadian forest industry over the 1970 to 1995 period (Lantz 2004). Using regression analysis, I found that a number of sectors and regions exhibited favourable value-added and variable cost trends over time.…”
Section: Research Contributions To Valuing Multiple Forest Outputs Mamentioning
confidence: 99%